Color steel tile coating with high weather resistance and water resistance and preparation process of color steel tile coating

By introducing toughening modifiers and black phosphorene nanosheet-nanocalcium carbonate composite materials into color steel tile coatings, the brittlement and aging problems of color steel tile coatings under temperature fluctuations and rainwater erosion are solved, and the effect of high weather resistance and water resistance is achieved, and the service life of color steel tile is extended.

CN120535997APending Publication Date: 2025-08-26深圳市深赛尔股份有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510448154.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-10
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

The existing color steel tile coatings are prone to brittleness and aging under different climatic conditions, and cannot effectively resist temperature fluctuations and rainwater erosion, resulting in waterproofing failure and shortening service life.

Method used

Using a combination of toughening modifier and nanocomposite materials, the toughening modifier is mixed with epoxy resin by mixing butyl acrylate, methyl methacrylate, etc. to form a covalent crosslinking network. The nanocomposite material forms a dense barrier layer through a composite material of black phosphorene nanosheets and nano calcium carbonate, which improves the high and low temperature resistance and water resistance of the coating.

Benefits of technology

It significantly improves the weather resistance and waterproofness of color steel tile coatings, extends the service life of color steel tile, reduces the risks of high-temperature softening and low-temperature embrittlement, and enhances the stability and corrosion resistance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120535997A_ABST
    Figure CN120535997A_ABST
Patent Text Reader

Abstract

The invention provides a color steel tile coating with high weather resistance and water resistance and a preparation process thereof, and belongs to the technical field of coating preparation. The preparation process comprises the following steps: preparing the toughening modifier; preparing a nano composite material; modifying the nano composite material by maleic anhydride; and preparing the color steel tile coating. Butyl acrylate, methyl methacrylate, glycidyl methacrylate, benzoyl peroxide and triphenylphosphine are mixed to prepare a premixed solution, then the premixed solution is mixed with epoxy resin E-51 for a reaction, a toughening modifier is prepared, after the toughening modifier is added into styrene-acrylic emulsion, a flexible chain segment in the toughening modifier allows a molecular chain segment to move at a low temperature, and the toughness of the styrene-acrylic emulsion is improved. The toughening modifier has the advantages that impact energy is absorbed, brittle fracture is reduced, and a rigid cross-linked network maintains a stable structure at high temperature, so that after the toughening modifier is added into styrene-acrylic emulsion to prepare the color steel tile coating, the high-temperature resistance can be effectively improved, and the weather resistance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coating preparation, and in particular to a color steel tile coating with high weather resistance and waterproofness and a preparation process thereof. Background Art

[0002] Colored steel tiles, with their advantages of light weight, easy installation, high cost-effectiveness, and excellent mechanical properties, have been widely used in many fields, including industrial plants, warehouses, temporary buildings, and agricultural facilities. In industrial scenarios, a large number of factories use colored steel tiles to build roofs and walls, providing shelter for production activities; warehouses constructed with colored steel tiles can be quickly completed and put into use, and efficiently store various materials; temporary buildings such as construction site dormitories and disaster relief housing, such as temporary buildings, are the preferred building material due to their rapid assembly and disassembly characteristics; and in agricultural facilities such as vegetable greenhouses and breeding houses, colored steel tiles help create a suitable production environment.

[0003] Color-coated steel tiles are typically coated with a specialized coating, typically composed of resin, pigment, filler, additives, and solvent. Resin is the film-forming substance that determines the coating's basic properties, such as adhesion and weather resistance. Pigments provide color and hiding power. Fillers improve the coating's physical properties and reduce costs. Additives adjust the coating's application properties and storage stability. Solvents dissolve the resin and other ingredients, ensuring good fluidity and coatability. The primary function of color-coated steel tile coatings is to protect them. Because color-coated steel tiles are typically made from thin steel sheets that undergo surface treatment and coating, while inherently corrosion-resistant, they are susceptible to atmospheric corrosion, rainwater erosion, and UV radiation over extended outdoor use, leading to rust and aging. The coating forms a protective film on the surface of the steel tiles, isolating them from the external environment and preventing oxygen, moisture, and other corrosive substances from reaching them. This slows corrosion and extends the life of the steel tiles.

[0004] However, due to the vastly different climatic conditions in different regions, color-coated steel tiles are subject to drastic temperature fluctuations. In the north during winter, temperatures often plummet to minus ten or even dozens of degrees Celsius. These low temperatures can make the protective coating formed by the paint on the color-coated steel tiles brittle, reducing its toughness and making it prone to cracking. In the summer, under the scorching sun in parts of the south, the surface temperature of the color-coated steel tiles can reach as high as 60 or 70 degrees Celsius. This high temperature accelerates the aging of the surface coating of the color-coated steel tiles, causing the coating to fade and powder, thereby weakening the protective effect of the color-coated steel tiles on the base metal and shortening their service life. In addition, if rainwater washes over the surface of the color-coated steel tiles for a long time and the coating has poor waterproof performance, moisture will gradually penetrate into the metal base, causing corrosion. Moreover, the thermal expansion and contraction of the color-coated steel tiles caused by temperature changes can easily lead to the failure of the waterproof performance, making it impossible to provide the color-coated steel tiles with long-term and reliable waterproof protection.

[0005] Therefore, it is necessary to propose a color steel tile coating with high weather resistance and waterproofness and a preparation process thereof to extend the service life of the color steel tile. Summary of the Invention

[0006] In view of the shortcomings of the prior art, the object of the present invention is to provide a color steel tile coating with high weather resistance and waterproofness and a preparation process thereof.

[0007] A preparation process for a color steel tile coating with high weather resistance and waterproofness comprises the following steps: S1: Preparation of toughening modifier A toughening modifier was prepared using butyl acrylate, methyl methacrylate, glycidyl methacrylate and epoxy resin E-51 as raw materials. S2: Preparation of nanocomposites Ultrasonic exfoliation of black phosphorus blocks produces a black phosphorene nanosheet dispersion, which is diluted with methanol and then added to a calcium hydroxide suspension. After sufficient dispersion, carbon dioxide gas is introduced to react and obtain a nanocomposite material. S3: Maleic anhydride modified nanocomposites Dissolving maleic anhydride and benzoyl peroxide in toluene, adding the nanocomposite material, and performing a reflux reaction to obtain a modified nanocomposite material; S4: Preparation of color steel tile coating Sodium lauryl sulfate and nonylphenol polyoxyethylene ether are dissolved in deionized water, and then styrene, butyl acrylate, acrylic acid and itaconic acid are added to prepare a pre-emulsion. Then, the pre-emulsion and initiator solution are used as raw materials to prepare a styrene-acrylic emulsion. Finally, epoxy resin emulsion, phthalic anhydride, the above-mentioned toughening modifier, modified nanocomposite material, triethanolamine, film-forming aid and defoaming agent are added to obtain a color steel tile coating.

[0008] Furthermore, S1 specifically includes the following steps: S1.1: Thoroughly stir and mix butyl acrylate, methyl methacrylate, glycidyl methacrylate, and benzoyl peroxide in a mass ratio of (15-16): (2.5-3.5): (3-4): 1, and then add 0.1 wt% triphenylphosphine to obtain a premixed solution; S1.2: Add 1 / 2 of the above premixed liquid to epoxy resin E-51, heat and stir at 80-85℃ for 1-2h, then add the remaining premixed liquid and chain transfer agent, continue to keep warm and react for 4-5h, then raise the temperature to 85-90℃, and add 0.1-0.2wt% hydroquinone and 0.05wt% phenothiazine to terminate the reaction. Remove the unreacted monomers in vacuo to obtain a toughening modifier.

[0009] Furthermore, S2 specifically includes the following steps: S2.1: Add bulk black phosphorus to N-methylpyrrolidone at a solid-liquid ratio of 1 g:(800-1000) mL. Ultrasonic exfoliate at 400-500 W for 6-8 h at 3-5°C. Centrifuge at 10,000-12,000 rpm for 20-30 min. Collect the supernatant and store in the dark to obtain a dispersion of black phosphorene nanosheets. S2.2: Add calcium oxide to methanol at a solid-liquid ratio of 1 g:(260-280) mL and stir at 400-500 rpm for 3-4 hours to obtain a calcium hydroxide suspension. Simultaneously, add the above-mentioned black phosphorene nanosheet dispersion to methanol at a volume ratio of 1:(6-8) and stir thoroughly to obtain a black phosphorene nanosheet dilution. S2.3: Add the above-mentioned black phosphorus nanosheet dilution to the above-mentioned calcium hydroxide suspension in a volume ratio of 1:(3-5), ultrasonically disperse for 20-30 minutes, then introduce carbon dioxide gas at 1-3 L / min for 10-20 minutes, and heat and stir at 50-60°C to react until the pH reaches 6-7. After centrifugal washing and vacuum drying, a nanocomposite material is obtained.

[0010] Furthermore, S3 specifically includes the following steps: S3.1: Add maleic anhydride and benzoyl peroxide to toluene at a solid-liquid ratio of (1.8-2) g: (0.08-0.1) g: (40-50) mL and stir thoroughly to dissolve to obtain a mixed solution. S3.2: Add the nanocomposite material prepared in step S2.3 to the above mixed solution, heat and stir under nitrogen atmosphere at 100-110°C for reflux reaction, cool, centrifuge and wash, and vacuum dry to obtain a modified nanocomposite material, wherein the mass ratio of maleic anhydride to nanocomposite material is 1:(6-10).

[0011] Furthermore, S4 specifically includes the following steps: S4.1: Add sodium lauryl sulfate and nonylphenol polyoxyethylene ether to deionized water and stir thoroughly to dissolve. Then add styrene, butyl acrylate, acrylic acid, and itaconic acid and stir for 20-30 minutes to obtain a pre-emulsion. S4.2: Prepare an initiator solution by dissolving potassium persulfate in deionized water at a solid-to-liquid ratio of 1 g:(30-34) mL. S4.3: Dissolve sodium bicarbonate in deionized water at a solid-liquid ratio of 1 g:(50-60) mL. Heat the mixture to 75-80°C while stirring and maintain. Add 1 / 8 of the pre-emulsion and 1 / 10 of the initiator solution. Stir for 20-30 minutes. Then, heat the mixture to 80-85°C and maintain. Add the remaining pre-emulsion and initiator solution dropwise over 2-3 hours while stirring. After the addition is complete, continue stirring and react for 1-2 hours. After cooling, add 25% aqueous ammonia to adjust the pH to 7-8. Filter the mixture to obtain a styrene-acrylic emulsion. S4.4: Add epoxy resin emulsion, phthalic anhydride, and the toughening modifier obtained in step S1.2 to the above-mentioned styrene acrylic emulsion, stir thoroughly, then add the modified nanocomposite material obtained in step S3.2, triethanolamine, film-forming aid and defoaming agent, continue stirring and dispersing for 20-30 minutes to obtain the color steel tile coating.

[0012] Furthermore, the mass of the epoxy resin E-51 is equal to that of the premixed liquid, the added amount of the chain transfer agent is 1-3% of the mass of the epoxy resin E-51, and the chain transfer agent is dodecyl mercaptan.

[0013] Furthermore, the pre-emulsion comprises, by mass, 20-30 parts of styrene, 20-30 parts of butyl acrylate, 3-5 parts of acrylic acid, 1-3 parts of itaconic acid, 0.5-1 part of sodium lauryl sulfate, 1-2 parts of nonylphenol polyoxyethylene ether and 45-55 parts of deionized water.

[0014] Furthermore, the mass ratio of the initiator solution to the pre-emulsion is 1:(8-10), and the mass ratio of sodium bicarbonate to potassium persulfate in the initiator solution is 1:(1.1-1.3).

[0015] Furthermore, the color steel tile coating includes, by mass: 35-45 parts of styrene acrylic emulsion, 15-25 parts of epoxy resin emulsion, 4-8 parts of phthalic anhydride, 6-10 parts of toughening modifier, 2-5 parts of modified nano-composite material, 0.5-1.5 parts of triethanolamine, 1.5-2.5 parts of film-forming aid and 0.1-0.3 parts of defoaming agent, wherein the film-forming aid is propylene glycol phenyl ether and the defoaming agent is a silicone defoaming agent.

[0016] Furthermore, a color steel tile coating with high weather resistance and waterproofness is prepared by the preparation process of a color steel tile coating with high weather resistance and waterproofness described in any of the above items.

[0017] Compared with the prior art, the present invention has at least the following beneficial effects: 1. The present invention prepares a premix by first mixing butyl acrylate, methyl methacrylate, glycidyl methacrylate, benzoyl peroxide and triphenylphosphine, and then mixing and reacting the premix with epoxy resin E-51 to prepare a toughening modifier. After adding the premix to the styrene acrylic emulsion, on the one hand, the toughening modifier can form a covalent cross-linking network with the styrene acrylic emulsion, thereby limiting the movement of molecular segments at high temperatures, increasing its heat deformation temperature, inhibiting high-temperature softening, and thus improving the high-temperature resistance of the coating. On the other hand, at low temperatures, the flexible segments in the toughening modifier provide flexibility to reduce overall brittleness. The flexible segments allow the molecular segments to move, absorb impact energy, and reduce brittle fracture. At high temperatures, the rigid groups provide rigidity compensation, balance high and low temperature performance, and the rigid cross-linking network maintains structural stability. Therefore, after the toughening modifier is added to the styrene acrylic emulsion to prepare the color steel tile coating, its high-temperature resistance can be effectively improved to enhance its weather resistance.

[0018] 2. The present invention prepares blocky black phosphorus first, adds it to N-methylpyrrolidone, and performs ultrasonic exfoliation to prepare a black phosphorene nanosheet dispersion. After diluting it with methanol, it is uniformly dispersed in a calcium hydroxide suspension, and carbon dioxide is introduced to react to prepare a black phosphorene nanosheet-nano-calcium carbonate nanocomposite material. After the surface is modified by maleic anhydride and added to a styrene-acrylic emulsion, the black phosphorene nanosheet has a large specific surface area and a unique layered structure, which will form a dense barrier layer during the emulsion film formation process to block the penetration of water molecules. After the nano-calcium carbonate and the black phosphorene nanosheet are composited, it not only helps to maintain the layered structure of black phosphorene, but also further increases the path length for water molecule penetration, improves the density of the coating, and thus achieves the effect of synergistically improving the waterproof performance of the color steel tile coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the present disclosure and, together with the description, further serve to explain the principles of the present disclosure and to enable one skilled in the relevant art to make and use the present disclosure.

[0020] Figure 1 This is a flow chart of the preparation process of the color steel tile coating with high weather resistance and waterproofness used in the embodiment of the present invention. DETAILED DESCRIPTION

[0021] The following describes in detail a color steel tile coating with high weather resistance and waterproofness and its preparation process provided by the present invention in conjunction with the accompanying drawings and specific embodiments.

[0022] Example 1

[0023] A preparation process for a color steel tile coating with high weather resistance and waterproofness, such as Figure 1 As shown, the following steps are included: S1: Preparation of toughening modifier S1.1: Thoroughly mix butyl acrylate, methyl methacrylate, glycidyl methacrylate, and benzoyl peroxide in a mass ratio of 15:2.5:3:1, and then add 0.1 wt% triphenylphosphine to obtain a premixed solution; S1.2: Add 1 / 2 of the above premix to epoxy resin E-51, heat and stir at 80°C for 1 hour, then add the remaining premix and chain transfer agent, continue to keep the reaction warm for 4 hours, then raise the temperature to 85°C, add 0.1wt% hydroquinone and 0.05wt% phenothiazine to terminate the reaction, and remove the unreacted monomers under vacuum to obtain a toughening modifier, wherein the mass of epoxy resin E-51 and the mass of the premix are equal, and the amount of chain transfer agent added is 1% of the mass of epoxy resin E-51, and the chain transfer agent is dodecyl mercaptan; S2: Preparation of nanocomposites S2.1: Add bulk black phosphorus to N-methylpyrrolidone at a solid-liquid ratio of 1 g:800 mL. Ultrasonic exfoliation is performed at 400 W for 6 h at 3°C. Centrifugation is then performed at 10,000 rpm for 20 min. The supernatant is collected and stored in the dark to obtain a dispersion of black phosphorene nanosheets. S2.2: Calcium oxide was added to methanol at a solid-liquid ratio of 1 g:260 mL and stirred at 400 rpm for 3 h to obtain a calcium hydroxide suspension. Simultaneously, the black phosphorene nanosheet dispersion was added to methanol at a volume ratio of 1:6. After thorough stirring and dispersion, a dilution of the black phosphorene nanosheets was obtained. S2.3: The black phosphorus nanosheet dilution was added to the calcium hydroxide suspension at a volume ratio of 1:3, and ultrasonic dispersion was performed for 20 minutes. Carbon dioxide gas was then introduced at 1 L / min for 10 minutes while heating and stirring at 50°C until the pH reached 6. The mixture was centrifuged, washed, and vacuum-dried to obtain a nanocomposite material. S3: Maleic anhydride modified nanocomposites S3.1: Add maleic anhydride and benzoyl peroxide to toluene at a solid-liquid ratio of 1.8 g:0.08 g:40 mL and stir thoroughly to dissolve to obtain a mixed solution. S3.2: Add the nanocomposite prepared in step S2.3 to the above mixed solution, heat and stir under nitrogen atmosphere at 100°C for reflux reaction, cool, centrifuge and vacuum dry to obtain a modified nanocomposite, wherein the mass ratio of maleic anhydride to nanocomposite is 1:6; S4: Preparation of color steel tile coating S4.1: Add 0.5 parts by mass of sodium lauryl sulfate and 1 part by mass of nonylphenol polyoxyethylene ether to 45 parts by mass of deionized water and stir thoroughly to dissolve. Then, add 20 parts by mass of styrene, 20 parts by mass of butyl acrylate, 3 parts by mass of acrylic acid, and 1 part by mass of itaconic acid and stir for 20 minutes to obtain a pre-emulsion. S4.2: Dissolve potassium persulfate in deionized water at a solid-liquid ratio of 1 g:30 mL to prepare an initiator solution, where the mass ratio of initiator solution to pre-emulsion is 1:8. S4.3: Dissolve sodium bicarbonate in deionized water at a solid-liquid ratio of 1 g:50 mL, and heat to 75°C while stirring and maintain the temperature. The mass ratio of sodium bicarbonate to potassium persulfate in the initiator solution is 1:1.1. Then, add 1 / 8 of the above pre-emulsion and 1 / 10 of the initiator solution, and stir for 20 minutes. Then, heat to 80°C and maintain the temperature. Add the remaining pre-emulsion and initiator solution dropwise over 2 hours while stirring. After the addition is complete, continue stirring and react for 1 hour. After cooling, add 25% ammonia water to adjust the pH to 7, and filter to obtain a styrene-acrylic emulsion. S4.4: Add 15 parts by mass of epoxy resin emulsion, 4 parts by mass of phthalic anhydride, and 6 parts by mass of the toughening modifier prepared in step S1.2 to 35 parts by mass of the above-mentioned styrene-acrylic emulsion, and after fully stirring, add 2 parts by mass of the modified nano-composite material prepared in step S3.2, 0.5 parts by mass of triethanolamine, 1.5 parts by mass of propylene glycol phenyl ether film-forming aid and 0.1-0.3 parts by mass of silicone defoamer, and continue stirring and dispersing for 20 minutes to obtain color steel tile coating, wherein the preparation method of the epoxy resin emulsion is: dissolve 2 parts by mass of nonylphenol polyoxyethylene ether in 8 parts by mass of deionized water to prepare an emulsifier solution, and then heat 40 parts by mass of epoxy resin E-51 to 50°C, and add the above-mentioned emulsifier solution and 70 parts by mass of deionized water while stirring, and continue stirring for 40 minutes to obtain the epoxy resin emulsion.

[0024] Example 2 A preparation process for a color steel tile coating with high weather resistance and waterproofness, such as Figure 1 As shown, the following steps are included: S1: Preparation of toughening modifier S1.1: Thoroughly mix butyl acrylate, methyl methacrylate, glycidyl methacrylate, and benzoyl peroxide in a mass ratio of 15.5:3:3.5:1, and then add 0.1 wt% triphenylphosphine to obtain a premixed solution; S1.2: Add 1 / 2 of the above premix to epoxy resin E-51, heat and stir at 82°C for 1.5 hours, then add the remaining premix and chain transfer agent, continue to keep the reaction warm for 4.5 hours, then raise the temperature to 87°C, add 0.15wt% hydroquinone and 0.05wt% phenothiazine to terminate the reaction, and remove the unreacted monomers under vacuum to obtain a toughening modifier, wherein the mass of epoxy resin E-51 and the mass of the premix are equal, and the amount of chain transfer agent added is 2% of the mass of epoxy resin E-51, and the chain transfer agent is dodecyl mercaptan; S2: Preparation of nanocomposites S2.1: Add bulk black phosphorus to N-methylpyrrolidone at a solid-liquid ratio of 1 g:900 mL. Ultrasonic exfoliation is performed at 450 W for 7 h at 4°C. The supernatant is then centrifuged at 11,000 rpm for 25 min. The supernatant is collected and stored in the dark to obtain a dispersion of black phosphorene nanosheets. S2.2: Calcium oxide was added to methanol at a solid-liquid ratio of 1 g:270 mL and stirred at 450 rpm for 3.5 h to obtain a calcium hydroxide suspension. Simultaneously, the black phosphorene nanosheet dispersion was added to methanol at a volume ratio of 1:7. After thorough stirring and dispersion, a dilution of the black phosphorene nanosheets was obtained. S2.3: The black phosphorus nanosheet dilution was added to the calcium hydroxide suspension at a volume ratio of 1:4, and ultrasonic dispersion was performed for 25 minutes. Carbon dioxide gas was then introduced at 2 L / min for 15 minutes while heating and stirring at 55°C until the pH reached 6.5. The mixture was centrifuged, washed, and vacuum dried to obtain a nanocomposite material. S3: Maleic anhydride modified nanocomposites S3.1: Add maleic anhydride and benzoyl peroxide to toluene at a solid-liquid ratio of 1.9 g:0.09 g:45 mL and stir thoroughly to dissolve to obtain a mixed solution. S3.2: Add the nanocomposite material obtained in step S2.3 to the above mixed solution, heat and stir under nitrogen atmosphere at 105°C for reflux reaction, cool, centrifuge and wash, and vacuum dry to obtain modified phenol polyoxyethylene ether dissolved in 8 parts by mass of deionized water to prepare an emulsifier solution, then heat 40 parts by mass of epoxy resin E-51 to 50°C, and add the above emulsifier solution and 70 parts by mass of deionized water while stirring, and continue stirring for 40 minutes to obtain epoxy resin emulsion.

[0025] Example 3

[0026] A preparation process for a color steel tile coating with high weather resistance and waterproofness, such as Figure 1 As shown, the following steps are included: S1: Preparation of toughening modifier S1.1: Thoroughly mix butyl acrylate, methyl methacrylate, glycidyl methacrylate, and benzoyl peroxide in a mass ratio of 15.5:3:3.5:1, and then add 0.1 wt% triphenylphosphine to obtain a premixed solution; S1.2: Add 1 / 2 of the above premix to epoxy resin E-51, heat and stir at 82°C for 1.5 hours, then add the remaining premix and chain transfer agent, continue to keep the reaction warm for 4.5 hours, then raise the temperature to 87°C, add 0.15wt% hydroquinone and 0.05wt% phenothiazine to terminate the reaction, and remove the unreacted monomers under vacuum to obtain a toughening modifier, wherein the mass of epoxy resin E-51 and the mass of the premix are equal, and the amount of chain transfer agent added is 2% of the mass of epoxy resin E-51, and the chain transfer agent is dodecyl mercaptan; S2: Preparation of nanocomposites S2.1: Add bulk black phosphorus to N-methylpyrrolidone at a solid-liquid ratio of 1 g:900 mL. Ultrasonic exfoliation is performed at 450 W for 7 h at 4°C. The supernatant is then centrifuged at 11,000 rpm for 25 min. The supernatant is collected and stored in the dark to obtain a dispersion of black phosphorene nanosheets. S2.2: Calcium oxide was added to methanol at a solid-liquid ratio of 1 g:270 mL and stirred at 450 rpm for 3.5 h to obtain a calcium hydroxide suspension. Simultaneously, the black phosphorene nanosheet dispersion was added to methanol at a volume ratio of 1:7. After thorough stirring and dispersion, a dilution of the black phosphorene nanosheets was obtained. S2.3: The black phosphorus nanosheet dilution was added to the calcium hydroxide suspension at a volume ratio of 1:4, and ultrasonic dispersion was performed for 25 minutes. Carbon dioxide gas was then introduced at 2 L / min for 15 minutes while heating and stirring at 55°C until the pH reached 6.5. The mixture was centrifuged, washed, and vacuum dried to obtain a nanocomposite material. S3: Maleic anhydride modified nanocomposites S3.1: Add maleic anhydride and benzoyl peroxide to toluene at a solid-liquid ratio of 1.9 g:0.09 g:45 mL and stir thoroughly to dissolve to obtain a mixed solution. S3.2: Add the nanocomposite material prepared in step S2.3 to the above mixed solution, heat and stir under reflux at 105°C under a nitrogen atmosphere, react, cool, centrifuge, wash, and vacuum dry to obtain a modified product. Then, add the remaining premixed solution and a chain transfer agent, continue to insulate and react for 5 hours, then raise the temperature to 90°C, add 0.2wt% hydroquinone and 0.05wt% phenothiazine to terminate the reaction, and remove unreacted monomers under vacuum to obtain a toughening modifier, wherein the mass of epoxy resin E-51 and the mass of the premixed solution are equal, and the amount of chain transfer agent added is 3% of the mass of epoxy resin E-51, and the chain transfer agent is dodecyl mercaptan; S2: Preparation of nanocomposites S2.1: Add bulk black phosphorus to N-methylpyrrolidone at a solid-liquid ratio of 1 g:1000 mL. Ultrasonic exfoliation is performed at 500 W for 8 h at 5°C. Centrifugation is then performed at 12,000 rpm for 30 min. The supernatant is collected and stored in the dark to obtain a dispersion of black phosphorene nanosheets. S2.2: Calcium oxide was added to methanol at a solid-liquid ratio of 1 g:280 mL and stirred at 500 rpm for 4 h to obtain a calcium hydroxide suspension. Simultaneously, the black phosphorene nanosheet dispersion was added to methanol at a volume ratio of 1:8. After thorough stirring and dispersion, a dilution of the black phosphorene nanosheets was obtained. S2.3: The black phosphorus nanosheet dilution was added to the calcium hydroxide suspension at a volume ratio of 1:5, and ultrasonic dispersion was performed for 30 minutes. Carbon dioxide gas was then introduced at 3 L / min for 20 minutes while heating and stirring at 60°C until the pH reached 7. The mixture was centrifuged, washed, and vacuum dried to obtain a nanocomposite material. S3: Maleic anhydride modified nanocomposites S3.1: Add maleic anhydride and benzoyl peroxide to toluene at a solid-liquid ratio of 2 g:0.1 g:50 mL and stir thoroughly to dissolve to obtain a mixed solution. S3.2: Add the nanocomposite material prepared in step S2.3 to the above mixed solution, heat and stir under nitrogen atmosphere at 110°C for reflux reaction, cool, centrifuge and vacuum dry to obtain a modified nanocomposite material, wherein the mass ratio of maleic anhydride to nanocomposite material is 1:10; S4: Preparation of color steel tile coating S4.1: Add 1 part by mass of sodium lauryl sulfate and 2 parts by mass of nonylphenol polyoxyethylene ether to 55 parts by mass of deionized water and stir thoroughly to dissolve. Then, add 30 parts by mass of styrene, 30 parts by mass of butyl acrylate, 5 parts by mass of acrylic acid, and 3 parts by mass of itaconic acid and stir for 30 minutes to obtain a pre-emulsion. S4.2: Dissolve potassium persulfate in deionized water at a solid-liquid ratio of 1 g:34 mL to prepare an initiator solution, where the mass ratio of initiator solution to pre-emulsion is 1:10. S4.3: Sodium bicarbonate was dissolved in deionized water at a solid-liquid ratio of 1 g:60 mL, and the temperature was raised to 80°C while stirring and maintained. The mass ratio of sodium bicarbonate to potassium persulfate in the initiator solution was 1:1.3. 1 / 8 of the above pre-emulsion and 1 / 10 of the initiator solution were added, and the mixture was stirred for 30 min. The temperature was then raised to 85°C and maintained. The remaining pre-emulsion and initiator solution were added dropwise over 3 h while stirring. After the addition was complete, the mixture was stirred and reacted for 2 h. After cooling, 25% aqueous ammonia was added to adjust the pH to 8, and the mixture was filtered to obtain a styrene-acrylic emulsion. S4.4: Add 25 parts by mass of epoxy resin emulsion, 8 parts by mass of phthalic anhydride, and 10 parts by mass of the toughening modifier prepared in step S1.2 to 45 parts by mass of the above-mentioned styrene-acrylic emulsion, and after fully stirring, add 5 parts by mass of the modified nano-composite material prepared in step S3.2, 1.5 parts by mass of triethanolamine, 2.5 parts by mass of propylene glycol phenyl ether film-forming aid, and 0.3 parts by mass of silicone defoamer, and continue stirring and dispersing for 30 minutes to obtain color steel tile coating, wherein the preparation method of the epoxy resin emulsion is: dissolve 3 parts by mass of nonylphenol polyoxyethylene ether in 10 parts by mass of deionized water to prepare an emulsifier solution, and then heat 50 parts by mass of epoxy resin E-51 to 60°C, and add the above-mentioned emulsifier solution and 80 parts by mass of deionized water while stirring, and continue stirring for 50 minutes to obtain the epoxy resin emulsion.

[0027] Comparative Example 1 The difference between this comparative example 1 and example 1 is that the toughening modifier in step S1 and step S4.4 is removed, and the other steps remain unchanged.

[0028] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the modified nanocomposite material in step S2-3 and step S4.4 is removed, and the other steps remain unchanged.

[0029] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that step S2 is removed, and the nanocomposite material in step S3.2 is replaced by an equal amount of black phosphorene nanosheets, while other steps remain unchanged.

[0030] Comparative Example 4 The difference between this comparative example 4 and Example 1 is that step S2 is removed, and the nanocomposite material in step S3.2 is replaced by an equal amount of nano-calcium carbonate, and the other steps remain unchanged.

[0031] Test Case Test 1: The color steel tile coatings prepared in Examples 1-3 and Comparative Example 1 were evenly coated on the steel plate. After curing, they were placed in high and low temperature test chambers at 150°C and -40°C, respectively. After heating at 150°C for 2 hours, the surface of the coating was observed for blistering, flowing, etc. After freezing at -40°C for 2 hours, the coating was bent at 270° to observe whether cracks, peeling, etc. appeared. The results are shown in Tables 1 and 2: Table 1: High temperature resistance test results of color steel tile coating Heat at 150℃ for 2h Example 1 No foaming, no flowing Example 2 No foaming, no flowing Example 3 No foaming, no flowing Comparative Example 1 Softening and blistering Table 2: Low temperature resistance test results of color steel tile coating -40℃ Freeze for 2h Example 1 No cracks, no peeling Example 2 No cracks, no peeling Example 3 No cracks, no peeling Comparative Example 1 Cracks appear It can be seen from Table 1 and Table 2 that in Comparative Example 1, when no toughening modifier is added, the coating formed by the prepared color steel tile paint softens and bubbles after being heated at 150°C for 2 hours, and cracks appear after being frozen at -40°C for 2 hours, indicating that its high and low temperature resistance is poor. It can be seen that by first mixing butyl acrylate, methyl methacrylate, glycidyl methacrylate and benzoyl peroxide to prepare a premix, and then mixing and reacting with epoxy resin E-51 to prepare a toughening modifier, and adding it to the styrene acrylic emulsion to prepare the color steel tile paint, the high temperature resistance of the color steel tile paint can be effectively improved, thereby improving the weather resistance of the color steel tile.

[0032] Test 2: The color steel tile coatings prepared in Examples 1-3 and 2-4 were evenly coated on the steel plate. After curing, the water resistance of the coating was tested according to GB / T9274-1988. The time for blistering, peeling, and gloss loss of the coating was recorded. The test was repeated three times and the average value was taken. The results are shown in Table 3: Table 3: Test results of water resistance of color steel tiles Water resistance (h) Example 1 186 Example 2 188 Example 3 185 Comparative Example 2 76 Comparative Example 3 124 Comparative Example 4 139 As can be seen from Table 3, when no modified nanocomposite material is added in Comparative Example 2, the water resistance of the color steel tile coating obtained is much lower than that of Example 1. This shows that by first preparing blocky black phosphorus, then adding it to N-methylpyrrolidone and ultrasonically exfoliating it to prepare a black phosphorene nanosheet dispersion, diluting it with methanol, and uniformly dispersing it in a calcium hydroxide suspension, and then introducing carbon dioxide to react to prepare a black phosphorene nanosheet-nano-calcium carbonate nanocomposite material. After surface modification with maleic anhydride and adding it to a styrene-acrylic emulsion, the water resistance of the color steel tile coating can be effectively improved. In addition, when single black phosphorene nanosheets or single nano-calcium carbonate are used to prepare the color steel tile coating in Comparative Examples 3 and 4, the water resistance of the obtained color steel tile coating is lower than that of the color steel tile coating prepared by using the black phosphorene nanosheet-nano-calcium carbonate nanocomposite material in Example 1. This shows that the composite of nano-calcium carbonate and black phosphorene nanosheets can synergistically improve the waterproof performance of the color steel tile coating.

[0033] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the present invention. Anyone skilled in the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by one of ordinary skill in the art without departing from the spirit and technical principles disclosed herein are intended to be covered by the claims of the present invention.

Claims

1. A process for preparing a color steel tile coating with high weather resistance and waterproofness, characterized in that: The steps include: S1: Preparation of toughening modifier A toughening modifier was prepared using butyl acrylate, methyl methacrylate, glycidyl methacrylate and epoxy resin E-51 as raw materials. S2: Preparation of nanocomposites Ultrasonic exfoliation of black phosphorus blocks produces a black phosphorene nanosheet dispersion, which is diluted with methanol and then added to a calcium hydroxide suspension. After sufficient dispersion, carbon dioxide gas is introduced to react and obtain a nanocomposite material. S3: Maleic anhydride modified nanocomposites Dissolving maleic anhydride and benzoyl peroxide in toluene, adding the nanocomposite material, and performing a reflux reaction to obtain a modified nanocomposite material; S4: Preparation of color steel tile coating Sodium lauryl sulfate and nonylphenol polyoxyethylene ether are dissolved in deionized water, and then styrene, butyl acrylate, acrylic acid and itaconic acid are added to prepare a pre-emulsion. Then, the pre-emulsion and initiator solution are used as raw materials to prepare a styrene-acrylic emulsion. Finally, epoxy resin emulsion, phthalic anhydride, the above-mentioned toughening modifier, modified nanocomposite material, triethanolamine, film-forming aid and defoaming agent are added to obtain a color steel tile coating.

2. The process for preparing a color steel tile coating with high weather resistance and waterproofness according to claim 1, characterized in that: S1 specifically includes the following steps: S1.1: Thoroughly stir and mix butyl acrylate, methyl methacrylate, glycidyl methacrylate, and benzoyl peroxide in a mass ratio of (15-16): (2.5-3.5): (3-4): 1, and then add 0.1 wt% triphenylphosphine to obtain a premixed solution; S1.2: Add 1 / 2 of the above premixed liquid to epoxy resin E-51, heat and stir at 80-85℃ for 1-2h, then add the remaining premixed liquid and chain transfer agent, continue to keep warm and react for 4-5h, then raise the temperature to 85-90℃, and add 0.1-0.2wt% hydroquinone and 0.05wt% phenothiazine to terminate the reaction. Remove the unreacted monomers in vacuo to obtain a toughening modifier.

3. The process for preparing a color steel tile coating with high weather resistance and waterproofness according to claim 2, characterized in that: S2 specifically includes the following steps: S2.1: Add bulk black phosphorus to N-methylpyrrolidone at a solid-liquid ratio of 1 g:(800-1000) mL. Ultrasonic exfoliate at 400-500 W for 6-8 h at 3-5°C. Centrifuge at 10,000-12,000 rpm for 20-30 min. Collect the supernatant and store in the dark to obtain a dispersion of black phosphorene nanosheets. S2.2: Add calcium oxide to methanol at a solid-liquid ratio of 1 g:(260-280) mL and stir at 400-500 rpm for 3-4 hours to obtain a calcium hydroxide suspension. Simultaneously, add the above-mentioned black phosphorene nanosheet dispersion to methanol at a volume ratio of 1:(6-8) and stir thoroughly to obtain a black phosphorene nanosheet dilution. S2.3: Add the above-mentioned black phosphorus nanosheet dilution to the above-mentioned calcium hydroxide suspension in a volume ratio of 1:(3-5), ultrasonically disperse for 20-30 minutes, then introduce carbon dioxide gas at 1-3 L / min for 10-20 minutes, and heat and stir at 50-60°C to react until the pH reaches 6-7. After centrifugal washing and vacuum drying, a nanocomposite material is obtained.

4. The process for preparing a color steel tile coating with high weather resistance and waterproofness according to claim 3, characterized in that: S3 specifically includes the following steps: S3.1: Add maleic anhydride and benzoyl peroxide to toluene at a solid-liquid ratio of (1.8-2) g: (0.08-0.1) g: (40-50) mL and stir thoroughly to dissolve to obtain a mixed solution. S3.2: Add the nanocomposite material prepared in step S2.3 to the above mixed solution, heat and stir under nitrogen atmosphere at 100-110°C for reflux reaction, cool, centrifuge and wash, and vacuum dry to obtain a modified nanocomposite material, wherein the mass ratio of maleic anhydride to nanocomposite material is 1:(6-10).

5. The process for preparing a color steel tile coating with high weather resistance and waterproofness according to claim 4, characterized in that: S4 specifically includes the following steps: S4.1: Add sodium lauryl sulfate and nonylphenol polyoxyethylene ether to deionized water and stir thoroughly to dissolve. Then add styrene, butyl acrylate, acrylic acid, and itaconic acid and stir for 20-30 minutes to obtain a pre-emulsion. S4.2: Prepare an initiator solution by dissolving potassium persulfate in deionized water at a solid-to-liquid ratio of 1 g:(30-34) mL. S4.3: Dissolve sodium bicarbonate in deionized water at a solid-liquid ratio of 1 g:(50-60) mL. Heat the mixture to 75-80°C while stirring and maintain. Add 1 / 8 of the pre-emulsion and 1 / 10 of the initiator solution. Stir for 20-30 minutes. Then, heat the mixture to 80-85°C and maintain. Add the remaining pre-emulsion and initiator solution dropwise over 2-3 hours while stirring. After the addition is complete, continue stirring and react for 1-2 hours. After cooling, add 25% aqueous ammonia to adjust the pH to 7-8. Filter the mixture to obtain a styrene-acrylic emulsion. S4.4: Add epoxy resin emulsion, phthalic anhydride, and the toughening modifier obtained in step S1.2 to the above-mentioned styrene acrylic emulsion, stir thoroughly, then add the modified nanocomposite material obtained in step S3.2, triethanolamine, film-forming aid and defoaming agent, continue stirring and dispersing for 20-30 minutes to obtain the color steel tile coating.

6. The process for preparing a color steel tile coating with high weather resistance and waterproofness according to claim 2, characterized in that: The mass of the epoxy resin E-51 is equal to that of the premixed liquid. The added amount of the chain transfer agent is 1-3% of the mass of the epoxy resin E-51, and the chain transfer agent is dodecyl mercaptan.

7. The process for preparing a color steel tile coating with high weather resistance and waterproofness according to claim 5, characterized in that: The pre-emulsion comprises, by mass, 20-30 parts of styrene, 20-30 parts of butyl acrylate, 3-5 parts of acrylic acid, 1-3 parts of itaconic acid, 0.5-1 part of sodium lauryl sulfate, 1-2 parts of nonylphenol polyoxyethylene ether and 45-55 parts of deionized water.

8. The process for preparing a color steel tile coating with high weather resistance and waterproofness according to claim 5, characterized in that: The mass ratio of the initiator solution to the pre-emulsion is 1:(8-10), and the mass ratio of sodium bicarbonate to potassium persulfate in the initiator solution is 1:(1.1-1.3).

9. The process for preparing a color steel tile coating with high weather resistance and waterproofness according to claim 5, characterized in that: Calculated by mass, the color steel tile coating includes: 35-45 parts of styrene acrylic emulsion, 15-25 parts of epoxy resin emulsion, 4-8 parts of phthalic anhydride, 6-10 parts of toughening modifier, 2-5 parts of modified nano-composite material, 0.5-1.5 parts of triethanolamine, 1.5-2.5 parts of film-forming aid and 0.1-0.3 parts of defoaming agent, among which the film-forming aid is propylene glycol phenyl ether and the defoaming agent is a silicone defoaming agent.

10. A color steel tile coating with high weather resistance and waterproofness, characterized in that: The color steel tile coating is prepared by the preparation process of the color steel tile coating with high weather resistance and waterproofness as described in any one of claims 1 to 9.